Do Bank Mergers Improve Performance? Evidence from Indian Bank’s Operational and Financial Metrics - K. Khasimpeera; S. Raghunatha Reddy (Involvement International Journal of Business, 2025)
Bank mergers are a common strategy to enhance operational and financial performance in the banking industry. This study aims to evaluate the impact of mergers on banks in India by measuring various financial and operational metrics before and after the merger. This research employs a quantitative approach using secondary data analysis from financial reports of merged banks. Data from the pre-merger and post-merger periods were collected to compare key performance indicators, such as Return on Assets (ROA), Return on Equity (ROE), Net Interest Margin (NIM), and operational efficiency ratio. A total of 10 merger cases over the last 10 years were analyzed using descriptive statistics and paired t-tests. The findings indicate that mergers positively impact several financial performance indicators. The average ROA increased from 0.85% to 1.25% within two years post-merger. ROE also rose by 2.5 percentage points. Additionally, operational efficiency improved, with the cost-to-income ratio decreasing from 48% to 43%. However, some banks experienced a decline in NIM from 3.2% to 2.9%, indicating challenges in maintaining profitability from interest-earning assets. These findings suggest that bank mergers in India generally provide benefits in terms of operational efficiency and profitability. However, the positive impact is not uniform, as some banks struggle to maintain net interest margins. Factors such as operational synergy, risk management, and regulatory policies play a role in post-merger outcomes. Bank mergers in India have a positive impact on financial and operational performance, despite certain challenges that need to be addressed. The findings of this study can serve as a reference for policymakers and bank management in designing more effective merger strategies in the future.